PENGEMBANGAN MEDIA SATUA BALI BERBASIS PODCAST UNTUK MENINGKATKAN KARAKTER SISWA KELAS III SEKOLAH DASAR - Sugita Utami, Ida Ayu Nyoman Trisna; Suartama, I Kadek; Wibawa, I Made Citra (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The purpose of this study is to detail the preparation and development of a Satua Bali product that is based on podcasts and is meant to help grade III elementary school children develop more capable individuals. The product's efficacy, validity, and practicality have all been evaluated. The ADDIE development model, which comprises of the analysis, design, development, implementation, and evaluation stages, serves as the basis for this study. A single group's pretest-posttest design is used in this study. The research object in this study is the validity, value, and efficacy of the media, and the development product under consideration is a podcast-based Satua Bali. Questionnaires are among the data gathering methods used in this study. The study's findings demonstrate that the validity test was conducted with good qualifications; the learning media expert test produced a score of 3.75. The score for the expert test on content and learning materials was 3.85. In addition, the replies from practitioners who met the practical qualifications were derived, yielding a score of 3.95. Additionally, the efficacy test resulted in a 0.001 < 0.005 result, indicating that the product substantially enhances the character of third-grade primary school pupils.